Greenhouse Environment of Hydroponics System for Broccoli Using Microcontroller Unit with SMS Notification: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research is more effective and efficient than farming when hydroponics is implemented in the country since this can help the greenhouse effect on the environment and can persuade other farmers or non-farmers to do greenhouse gardening in their houses, yards, or outside their houses. The way the researchers conducted our project study, they acquired facts and merged ideas about the concept in this project, which can help grow broccoli inside and outside the house; each has more nutrients that can be harvested in three to four months. It can be lucrative even when they are only grown at home. It outlines the findings taken from the investigation, in which the researcher measured temperature, water level, and broccoli growth. Plants need water, sunlight, carbon dioxide, and nutrients to develop. Thus, growing plants without soil is a great approach to nurturing many food plants. In hydroponics, growers use a microcontroller to operate the electronics to manage the monitoring of plants. The respondents who were involved in the design project were the broccoli farmers. A total of 109 respondents were involved in the survey, with 69 males and 40 females. The Study is an innovative and appropriate method of planting broccoli and other vegetables. By this design, you people know that what they have planted is healthy and nutritious because this design provided information through a text message that would help you to know that what was planted is nutritious. The components that researchers used helped to improve the design, like Arduino Microcontroller, Pump motor, Water level sensor, Moisture sensor, Temperature sensor, LCD, and Device.
Keywords: Greenhouse Environment; Hydroponics; Broccoli; Arduino; Water Level Sensor; Moisture Sensor; Temperature Sensor